A poloxamer-polypeptide thermosensitive hydrogel as a cell scaffold and sustained release depot. Issue 17 (11th April 2016) - Lin, Ji-Yu; Lai, Po-Liang; Lin, Yuan-Kai; Peng, Sydney; Lee, Li-Yu; Chen, Chieh-Nan; Chu, I-Ming
Abstract : Herein, we report the synthesis and characterization of a novel positively charged thermosensitive hydrogel prepared from poloxamer (PLX)-poly(l -alanine-lysine) (Lys-Ala-PLX-Ala-Lys) that demonstrates potential in biomedical applications including tissue engineering and drug delivery. Abstract : Herein, we report the synthesis and characterization of a novel positively charged thermosensitive hydrogel prepared from poloxamer (PLX)-poly(l -alanine-lysine) (Lys-Ala-PLX-Ala-Lys) that demonstrates potential in biomedical applications including tissue engineering and drug delivery. At a dilute concentration, the copolymer self-assembled into micelles that were sensitive to temperature elevation. In the concentration range of 3–7 wt%, the aqueous copolymer solution underwent sol–gel transition near the physiological temperature and exhibited changes in its secondary structure content, as evidenced by FT-IR. Excellent viability of cells cultured within the scaffold was observed after 72 h of incubation. On the other hand, negatively charged bovine serum albumin was incorporated into the hydrogel without diminishing material integrity. Over the course of seven days, the protein underwent extended zero-order release. These findings highlight the potential of this system as a cell scaffold as well as a depot for the extended delivery of drugs and proteins, specifically those which bear a charge opposite to that of the hydrogel.